Visual discrimination learning impairments produced by combined transections of the anterior temporal stem, amygdala and fornix in marmoset monkeys. - Maclean, C; Gaffan, D; Baker, H; Ridley, R (2001)
Marmoset monkeys (Callithrix jacchus) with bilateral transections of the anterior temporal stem, amygdala and fornix were unable to relearn a 2-choice object discrimination first learnt prior to surgery, and were very severely impaired at relearning a concurrent object discrimination task which they had learnt and relearnt prior to surgery, indicating that they had a dense retrograde amnesia. They also had difficulty learning new visual object discriminations but were only mildly impaired on spatial learning. When tested on new learning of concurrent discriminations 8 to 10 weeks after surgery, three operated monkeys were unable to reach criterion in 400 trials while the remaining two operated monkeys performed within the normal range. The operated monkeys were subsequently shown to be impaired on acquisition of shape discriminations using black objects. These anterograde effects suggest that the impairment runs mainly in the domain of visual analysis. The monkeys also exhibited many of the features of the Klüver-Bucy syndrome. Histological analysis indicated that in addition to cutting some of the subcortical temporal lobe efferent pathways, the surgical procedures had cut the cholinergic afferents to the temporal neocortex, entorhinal cortex, and hippocampus. In a second experiment we found that treatment with the cholinergic agonist pilocarpine, which is effective in monkeys with specific cholinergic lesions, was unable to remediate the lesion-induced impairments. This suggests that transection of the non-cholinergic afferents, or the temporal lobe subcortical efferents, contributed to the behavioural syndrome and the learning and retention deficits seen in these monkeys.